Haemodynamic Changes in Patients Undergoing Coronary Stenting for Miocardial Infarction (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Acute Coronary Syndrome or ACS in short has become a bread and butter case scenario seen in every hospital over the whole world with increasing industrialization and people depending more on fast food based diet and less exercise. ACS was previously known as Myocardial Infarction which in technicalities means rupture of plaque formation in the coronary arteries. It is associated with atherosclerosis and hyperlipidemia. As well as increased lipolysis forming Plaque and Emboli (can be septic also). Problems are exacerbated by other co morbidities like hypertension, Diabetes, calcification of the vessels. For management part, thrombolysis is used followed by PCI.